Introducing B-Sweep: An Innovative Bird-Repelling Device Powered by Solar Cells and Sound Waves, Efficiently Protecting Against Bird Strikes in Airport Airsides - Muhammad Rafli Fazal; Direstu Amalia; Jasmin Masyirianti; Akbar Nopriansyah Saputra; Yudhistira Agung Mahendra; Muhammad Khafid Ridwan; Sukahir Sukahir; Yeti Komalasari (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The study aims to create a bird-repelling device called Bird-repelling with solar cell and sound wave energy efficient protection (B-SWEEP) to reduce the likelihood of bird strikes. The study employs a Research and Development (R&D) methodology, whereby data is gathered through a site survey to identify bird-highlighted places, including documentation of the quantity and variety of birds observed during a specific timeframe at the Politeknik Penerbangan Palembang—analysis conducted by measuring the range and power consumption effectiveness. The findings indicate that B-SWEEP generated sound waves at a distance of 100 meters with a maximum frequency of 500 Hz. The B-SWEEP test field is used six times, with a five-meter buffer between each experiment and the user. The purpose is to evaluate how well B-SWEEP can receive Wi-Fi. This test enables us to determine the distance at which B-SWEEP began to perform poorly when the user gave commands, and it helps improve B-SWEEP even further as a result of this research. It demonstrates how B-SWEEP deters birds in a field. Using solar panels for charging, B-SWEEP can function without electricity for one hour. Using an ESP32-CAM microcontroller to implement Internet of Things (IoT) technologies. Airport managers can recognize the kinds of birds that fly into the airside area with the help of this micro camera, including sparrows that are immediately linked to a telephone. Due to its sound and wave, the sweep audio signal might deter birds from nesting and visiting the airport airside. Integrating IoT-based automation technologies with renewable energy sources can facilitate the execution of the eco-airport initiative. Based on testing results and feedback from 51 respondents, improvements to B-SWEEP include enhancing usability by simplifying interface complexity and adjusting visual elements for greater appeal. Furthermore, expanding its capabilities to repel a wider range of animals through tailored ultrasonic technology would enhance its effectiveness and user satisfaction, making B-SWEEP a more versatile solution.